2015
DOI: 10.21608/jpp.2015.51753
|View full text |Cite
|
Sign up to set email alerts
|

Improving Yield and Fruit Quality of Washington Navel Orange Using Foliar Applications of Some Natural Biostimulants.

Abstract: Field experiment was carried out during two successive seasons of 2012 and 2013 on Washington Navel sweet orange cultivar (Citrus sinemsis, L) onto sour orange rootstock (C. aurantium , L) grown in well drainage clay loam soil of a commercial orchard located in Shiwah Valley (30°51'55.78"N, 31°16'23.14"E), near Aga city, Dakahleia Governorate, Egypt. The investigation was designed to throw some light on the effect of two natural biostimulants, i.e., Milagrow at 10, 15 and 20 ppm (extracted from pollen grains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Plants treated with silicon at 3% and sprayed with yeast at 20g/l level, bloom earlier by about 20 days compared to the control. These results are in agreement with those obtained by Abd-El- Hamied (2015), Ahmed et al, 2013 andRoshdy (2014) and El-Boray et al, (2015) on other plant species.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Plants treated with silicon at 3% and sprayed with yeast at 20g/l level, bloom earlier by about 20 days compared to the control. These results are in agreement with those obtained by Abd-El- Hamied (2015), Ahmed et al, 2013 andRoshdy (2014) and El-Boray et al, (2015) on other plant species.…”
Section: Resultssupporting
confidence: 93%
“…The high own content of yeast extract from nutrients as well as amino acids, vitamins and phytohormones surely reflected on enhancing the biosyntheses of pigments and total carbohydrates consequently advancing fruit quality (Soliman et al 2000). These results are in agreement with those reported by El-Shazly and Mustafa (2013) and El-Boray et al (2015) with Neval orange who reported that active dry yeast caused a significant increases in T.S. and vitamin C content of fruits.…”
Section: -Fruit Qualitysupporting
confidence: 93%
See 1 more Smart Citation
“…Orange occupies the first rank among all fruits cultivated in Egypt, with about more than four million metric tons produced in 2015 (El-Boray et al, 2015), and Egypt exports of orange exceeded 1.6 million tons in /2017(USDA 2016, 2017. Navel orange is the most important citrus fruit in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Also natural raw material mixture and natural raw potassium (feldspar) are a good alternative to reduce uses of chemical fertilizers (Abdel Rahman et al, 2009 andEman et al, 2010). In this respect, several studies were accomplished for producing organic fruits through avoiding partially the application of chemicals fertilizers and encouraging the application of organic and natural raw material (rocks) fertilizers ( El-Boray et al,2007, Abdel-Hak et al, 2012, Shaheen et al, 2013, El-Iraqy 2014, El-Boray et al .,2015and Mostafa and Abdel Rahman 2015.…”
Section: Introductionmentioning
confidence: 99%